THE EFFECT OF EXPERIENTIAL MARKETING AND PSYCHOLOGICAL PRICING ON REPURCHASE INTENTION OF CUSTOMERS IN STORE X - Poetri M.O. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Increasingly sophisticated technology makes it easy for consumers to find everything they are looking for in a short time. The increasing competition requires marketers to have new marketing methods that are different from competitors. Experiential marketing is a topic that has been widely discussed by marketers to attract consumer's attention. Schmitt (1999) explains that experiential marketing is a marketing and management method that is driven by the experience of consumers. Consumers who feel great experiences when purchase, will produce customer satisfaction and loyalty so that it will form consumer repurchase intentions. Pride & Ferrel (Ahmed & Baruah, 2017) said psychological pricing is determined to influence consumer emotions in making decisions related to purchasing. Farisya’s research (2012) shows that there is an influence of experiential marketing on repurchase intentions. However, there are still few studies that discuss the effect of psychological pricing on the repurchase intention variable. This study aims to examine the effect of experiential marketing and psychological pricing on repurchase intentions. This research was conducted on consumers who have made purchases at store X, the number of participants was 72 people. This study uses an experiential marketing scale (Schmitt, 1999), repurchase intention scale (adapted Farisya, 2012) and psychological pricing scale compiled by researchers based on Larson’s theory (2014).